2017
DOI: 10.1186/s13287-017-0702-3
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative potential of primary adult human neural stem cells on micropatterned bio-implants boosts motor recovery

Abstract: BackgroundThe adult brain is unable to regenerate itself sufficiently after large injuries. Therefore, hopes rely on therapies using neural stem cell or biomaterial transplantation to sustain brain reconstruction. The aim of the present study was to evaluate the improvement in sensorimotor recovery brought about by human primary adult neural stem cells (hNSCs) in combination with bio-implants.MethodshNSCs were pre-seeded on implants micropatterned for neurite guidance and inserted intracerebrally 2 weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…To evaluate maximal forelimb muscle grip strength, the animals grasped a horizontal bar of the Grip Strength Meter (Bioseb, France) attached to a dynamometer, and then they were gently pulled away by an experienced handler until their grasp was broken. This test was validated in previous studies by the group (19, 21, 23). The dynamometer measured the maximal isometric force before the animal released the bar.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…To evaluate maximal forelimb muscle grip strength, the animals grasped a horizontal bar of the Grip Strength Meter (Bioseb, France) attached to a dynamometer, and then they were gently pulled away by an experienced handler until their grasp was broken. This test was validated in previous studies by the group (19, 21, 23). The dynamometer measured the maximal isometric force before the animal released the bar.…”
Section: Methodsmentioning
confidence: 90%
“…The lesioned hemisphere was the dominant one. The stereotaxic coordinates targeted, were: AP −1.5 mm, ML +3.2 mm, DV −5.3 mm (20), as previously determined from primary motor cortically injured rat brain slices with evidence of corticospinal tract degeneration (21). After the injection, the needle was left in place for additional 4 min to avoid backflow.…”
Section: Methodsmentioning
confidence: 99%
“…25 Still in the context of neuronal cell culture, it has been shown that oriented scaffolds are able to guide the development of neurites and axons in one preferential direction and can help in a suitable tissue reconstruction. [26][27][28] Thus, for the scaffolding purpose, and also more generally for extending the scope of LMWG applications, our objective was to explore how fluidics (or microfluidics) can drive the self-assembly of the gelator into well-defined structures and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported significant motor recovery and increased cell survival 3 weeks after implantation compared to the sham animals (Vaysse et al, 2015). In a follow-up publication, the host response to the scaffold was analyzed: there was no significant increase in activated ED1-positive microglia at the implant site and surprisingly a decrease in the astrogliosis response compared to the sham (Davoust et al, 2017), suggesting that the implant is well tolerated long-term. Future studies could also focus on combining topographical cues with some of the factors discussed in previous sections known to promote connectivity and plasticity in the brain (Wei et al, 2007;Bliss et al, 2010).…”
Section: Axon Guidance and Synapse Formationmentioning
confidence: 97%